Assessment of knowledge, attitude and practice of antenatal mothers on child’s immunization in Raichur district, Karnataka - Ramalingam, Revathi; Ajay, J; Chetty, Sanjeev (Indian Journal of Child Health, 2017)
Objectives: To assess the knowledge, attitude and practice (KAP) of antenatal mothers on child’s immunization and to know the factors affecting the completeness of vaccination and coverage. Design: A questionnaire based cross-sectional study. Setting: Navodaya Hospital, Raichur in the months of June and July 2016. Participants: 200 antenatal inpatients and outpatients mothers. Intervention: A questionnaire comprising 18 questions were administered to the mothers to assess their KAP regarding child’s immunization. Their responses were analyzed using Chi-square test with a value of p